The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5603/fm.a2021.0106
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical observation and significance of the parietal foramen in Chinese adults

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In some studies, it was noted that this foramen may be 3 or more in number [4,8,9,17,26,30]. Liu et al [12] stated that all the PFs they observed were singles. Murlimanju et al [17] 4).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In some studies, it was noted that this foramen may be 3 or more in number [4,8,9,17,26,30]. Liu et al [12] stated that all the PFs they observed were singles. Murlimanju et al [17] 4).…”
Section: Resultsmentioning
confidence: 98%
“…The prevalence of PF varies between 50% (USA) and 86% (Thailand) in different ethnic groups [14,30]. The frequency of bilateral PF ranged from 24.2% (European) to 74.65% (Turkey), while the frequency of unilateral PF ranged from 20.2% (African) to 66.07 (Chinese) right side and 63.21 (Chinese) left side [8, 12,27]. Similarly, the frequency of PF on the SS ranged from 0.7% (Japan) to 33.7% (Turkey) [8,15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations